Exploring the Frontier of Biopolymer-Assisted Drug Delivery: Advancements, Clinical Applications, and Future Perspectives in Cancer Nanomedicine - Alharbi HM (Dove Medical Press, 2024)
Hanan M Alharbi Department of Pharmaceutical Sciences, College of Pharmacy, Umm Al-Qura University, Makkah, Saudi ArabiaCorrespondence: Hanan M Alharbi, Department of Pharmaceutics, Faculty of Pharmacy, Umm Al-Qura University, Makkah, 21955, Saudi Arabia, Email hmsharbi@uqu.edu.saAbstract: The burgeoning global mortality rates attributed to cancer have precipitated a critical reassessment of conventional therapeutic modalities, most notably chemotherapy, due to their pronounced adverse effects. This reassessment has instigated a paradigmatic shift towards nanomedicine, with a particular emphasis on the potentialities of biopolymer-assisted drug delivery systems. Biopolymers, distinguished by their impeccable biocompatibility, versatility, and intrinsic biomimetic properties, are rapidly ascending as formidable vectors within the cancer theragnostic arena. This review endeavors to meticulously dissect the avant-garde methodologies central to biopolymer-based nanomedicine, exploring their synthesis, functional mechanisms, and subsequent clinical ramifications. A key focus of this analysis is the pioneering roles and efficacies of lipid-based, polysaccharide, and composite nano-carriers in enhancing drug delivery, notably amplifying the enhanced permeation and retention effect. This examination is further enriched by referencing flagship nano formulations that have received FDA endorsement, thereby underscoring the transformative potential and clinical viability of biopolymer-based nanomedicines. Furthermore, this discourse illuminates groundbreaking advancements in the realm of photodynamic therapy and elucidates the implications of advanced imaging techniques in live models. Conclusively, this review not only synthesizes current research trajectories but also delineates visionary pathways for the integration of cutting-edge biomaterials in cancer treatment. It charts a course for future explorations within the dynamic domain of biopolymer-nanomedicine, thereby contributing to a deeper understanding and enhanced application of these novel therapeutic strategies.Keywords: theragnostic, nanomedicines, antitumor, drug delivery, nanotherapeutic, anticancer, biopolymers